2010
DOI: 10.1097/qai.0b013e3181d82ce5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Second-Generation Circulating Recombinant Form (CRF48_01B) in Malaysia: A Descendant of the Previously Identified CRF33_01B

Abstract: A molecular epidemiological investigation conducted among injecting drug users in eastern Peninsular Malaysia in 2007 identified a cluster of sequences (n = 3) located outside any known HIV-1 genotype. Analyses of near full-length nucleotide sequences of these strains from individuals with no recognizable linkage revealed that they have an identical subtype structure comprised of CRF01_AE and subtype B', distinct from any known circulating recombinant forms (CRFs). This novel CRF, designated CRF48_01B, is clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…Nonetheless, socially and/or virologically low barriers to recombination are suggested by the large number of reports in the past decade of more than 10 different types of CRFs between B and AE in Asian countries. [3][4][5][6][7][8][9][10][11][12][13][14] In conclusion, a new recombinant strain CRF69_01B was found in Japan. This discovery alerts stakeholders to the important need for continued surveillance of circulating HIV Tables S2B and S3, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, socially and/or virologically low barriers to recombination are suggested by the large number of reports in the past decade of more than 10 different types of CRFs between B and AE in Asian countries. [3][4][5][6][7][8][9][10][11][12][13][14] In conclusion, a new recombinant strain CRF69_01B was found in Japan. This discovery alerts stakeholders to the important need for continued surveillance of circulating HIV Tables S2B and S3, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…S2), which differed from any previously reported AE/B recombinant forms. [3][4][5][6][7][8][9][10][11][12][13][14] The requirement for declaring a new CRF, as proposed by the Los Alamos National Laboratory in 1999, is to have at least three cases with no direct epidemiological lineage, accompanied by near full-length sequences. 32,33 From the medical records of the cases we confirmed that K231, K320,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we identified and characterized two novel recombinants derived from subtype B and CRF01_AE, which were highly different from the previously reported CRF01_AE/B recombinant. [4][5][6][7][8] Plasma samples were collected from two HIV-positive MSM from an IRB approved study conducted by China CDC. Both of them were infected with HIV-1 through MSM, and were confirmed as HIV-1 seropositive in May 2013 for BJMP3037B and in September 2013 for BJMP3194B, respectively.…”
mentioning
confidence: 99%
“…In Thailand and Malaysia, emergence of distinct CRF01_AE/B circulating recombinant forms (CRFs) was documented mainly among injection drug users. [1][2][3][4] A recent HIV-1 molecular epidemiology study in Singapore was performed to determine if there was any cross-border transmission of the newly identified CRFs. 5 Unexpectedly, a novel recombinant form, with subtype B in protease and gp41 and CRF01_AE in gp120, was identified in 13 (11.9%) of 109 individuals tested.…”
mentioning
confidence: 99%